Determinan Kepatuhan Santri terhadap Protokol Kesehatan Covid-19 - Fauziyah, Safira Aufi; Pawenang, Eram Tunggul (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Implementation of health protocols during the COVID-19 pandemic is required by the government. Islamic boarding schools can become clusters for the spread of COVID-19 so that the RI Minister of Health issued Decree No.HK.01.07/MENKES/2322/2020. The purpose of this study was to determine the factors that influence student compliance in implementing the COVID-19 health protocol. Methods Analytic observational study with a cross-sectional design. The sampling technique is Probability Sampling with Simple Random Sampling. The sample is 92 respondents. The research instrument was in the form of questionnaires and observation sheets. Independent variables: gender, comorbidities, knowledge, use of masks, CTPS, physical distancing, cough-sneeze ethics, monitoring by the authorities, bedroom size, and CTPS facilities, and dependent variable: compliance to health protocols. Data analysis with Chi Square test and Logistic Regression. Results: Results of the Chi-Square Test analysis: use of masks (p=0.001), CTPS (p=0.001), physical distancing (p=0.001), cough-sneeze ethics (p=0.001), and monitoring by the authorities (p=0.001). The most dominant factor affecting the COVID-19 health protocol for students is monitoring by the authorities (RP = 0.272). Conclusion: There is a need for monitoring by the authorities and empowering the Islamic boarding school community regarding the implementation of health protocols.